Gel-impregnated porous copper self-lubricating bearing retainer material as well as preparation method and application thereof
By immersing supramolecular gel lubricant in porous copper, the immersed gel porous copper self-lubricating bearing cage material is formed, and the problems of low oil content and oil retention in the prior art are solved, high oil content and high oil retention are achieved, and lubricating performance and service life of the bearing are significantly improved.
Patent Information
- Application Number
- CN202411833555.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing oil-containing bearing cage materials have low oil content and oil retention, especially when the bearings are running at high speed, which limits their use range and affects the lubrication effect and service life.
Using impregnated gel porous copper self-lubricating bearing cage material, a high oil content and high oil retention material is formed by immersing supramolecular gel lubricants in the porous copper, including base oils and gel factors such as N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucosamide and bis(stearate) aluminum lipoate.
The oil content and oil retention rate of the material are significantly improved, especially at high speeds, the oil retention rate can reach about 90%, enhance the lubricating performance and extend the service life of the bearing.
Smart Images

Figure BDA0005186129610000041 
Figure HDA0005186129630000011 
Figure HDA0005186129630000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating materials, and in particular to a gel-impregnated porous copper self-lubricating bearing cage material and a preparation method and application thereof. Background Art
[0002] With the development of modern science and technology, high-precision mechanical components are widely used in many fields such as aerospace, electronic manufacturing, etc. These fields have extremely high requirements on the precision and stability of mechanical components, and put forward more stringent requirements on reducing the negative impact of friction and wear.
[0003] There is a risk of leakage of liquid lubricants during the use of equipment, which will not only cause waste of lubricants or even lubrication failure, but may also pollute the environment and other components around the equipment. The leakage of liquid lubricants poses a potential pollution to the environment. If liquid lubricants enter water or soil, they will cause harm to the environment. In order to solve the sealing problem of the lubrication system, some oil-containing self-lubricating materials have been developed. The related technology discloses a metal-polymer composite oil-containing bearing retainer material. The oil-containing bearing retainer itself can store and release lubricating oil, and can continuously provide lubrication for bearings and other components during the operation of the equipment. However, the oil content and oil retention rate of current oil-containing bearing retainer materials are still relatively low, and there is a problem of high oil loss when the bearing runs at high speed, which not only limits its scope of use, but also seriously affects the lubrication effect and service life of the bearing. Summary of the invention
[0004] In view of this, the present invention provides a gel-impregnated porous copper self-lubricating bearing cage material and a preparation method and application thereof. The gel-impregnated porous copper self-lubricating bearing cage material provided by the present invention has a high oil content and a high oil retention rate, and has more excellent tribological properties.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A gel-impregnated porous copper self-lubricating bearing cage material comprises porous copper and a supramolecular gel lubricant impregnated into the pores of the porous copper; the supramolecular gel lubricant comprises a base oil and a gel factor; the gel factor comprises one or two of N-dodecyl-2,4-(3,4-dichlorobenzylidene)-D-glucamide and aluminum bis(stearate) lipoate; the porosity of the porous copper is above 30%.
[0007] Preferably, the pore size of the porous copper is in the micrometer level; the porosity of the porous copper is 30-70%.
[0008] Preferably, the method for preparing the porous copper preferably comprises the following steps: mixing copper powder and iron powder and sintering them to obtain a copper-iron precursor; and soaking the copper-iron precursor in an acid solution to obtain the porous copper.
[0009] Preferably, the base oil includes one or more of PAO4, PAO10, 150SN and 500SN.
[0010] Preferably, the mass percentage of the gel factor in the supramolecular gel lubricant is 1-10%.
[0011] Preferably, when the gel factor is N-dodecyl-2,4-(3,4-dichlorobenzylidene)-D-glucamide, the mass percentage of the gel factor in the supramolecular gel lubricant is 2-3%; when the gel factor is aluminum bis(stearate) lipoate, the mass percentage of the gel factor in the supramolecular gel lubricant is 5-6%.
[0012] The present invention also provides a method for preparing the impregnated porous copper self-lubricating bearing cage material described in the above scheme, comprising the following steps:
[0013] heating and mixing the gel factor and the base oil to obtain a gel factor oil solution;
[0014] The porous copper is immersed in the gel factor oil solution and then cooled to obtain the gel-impregnated porous copper self-lubricating bearing cage material.
[0015] Preferably, the temperature of the heating and mixing is 170-190° C., and the time is 15-30 minutes.
[0016] Preferably, the immersion temperature is above 160° C., the vacuum degree is below -0.8 bar, and the immersion time is 4 to 10 hours.
[0017] The present invention also provides the use of the impregnated porous copper self-lubricating bearing cage material described in the above scheme or the impregnated porous copper self-lubricating bearing cage material prepared by the preparation method described in the above scheme in the lubrication of mechanical parts.
[0018] The present invention provides a gel-impregnated porous copper self-lubricating bearing cage material, comprising porous copper and a supramolecular gel lubricant impregnated into the pores of the porous copper; the supramolecular gel lubricant comprises a base oil and a gel factor; the gel factor comprises one or two of N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide bis(stearate) lipoic acid aluminum; the porosity of the porous copper is above 30%. The porous copper of the present invention has a higher porosity, can store more lubricants, and has a higher oil content; the gel factor used in the present invention can form a three-dimensional network structure through non-covalent action, realize efficient capture of the base oil, and thus effectively avoid the loss of lubricant inside the porous copper. Compared with ordinary oil-containing cages, the gel-impregnated porous copper self-lubricating bearing cage material of the present invention greatly improves the oil retention rate. The results of the embodiment show that when the gel factor is aluminum bis(stearate) lipoate, the oil retention rate of the impregnated porous copper self-lubricating bearing cage material of the present invention at high speed can reach about 90%; in addition, the phase transition temperature of the gel factor used in the present invention is above 150°C, and the applicable temperature range of the obtained impregnated porous copper self-lubricating bearing cage material is wide. In summary, the impregnated porous copper self-lubricating bearing cage material provided by the present invention has high oil content and oil retention rate, has more excellent lubrication performance, can be used in various bearings to avoid lubricant loss and improve bearing lubrication performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The friction coefficient of the self-lubricating bearing retainer material prepared in Example 1, Example 3 and Comparative Example 1 is a trend diagram over time;
[0020] Figure 2 The friction coefficient of the self-lubricating bearing retainer material prepared in Example 2, Example 4 and Comparative Example 2 is a trend diagram over time;
[0021] Figure 3 The oil retention test results of the self-lubricating bearing cage materials prepared in Example 1, Example 3 and Comparative Example 1 at different speeds;
[0022] Figure 4 The oil retention rate test results of the self-lubricating bearing cage materials prepared in Example 2, Example 4 and Comparative Example 2 at different rotation speeds. DETAILED DESCRIPTION
[0023] The invention provides a gel-impregnated porous copper self-lubricating bearing cage material, comprising porous copper and a supramolecular gel lubricant impregnated into pores of the porous copper; the supramolecular gel lubricant comprises a base oil and a gel factor; the gel factor comprises one or two of N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide and aluminum bis(stearate) lipoate; the porosity of the porous copper is above 30%.
[0024] The impregnated porous copper self-lubricating bearing cage material provided by the present invention includes porous copper. In the present invention, the pore size of the porous copper is preferably micrometer-level, more preferably 0.5-20 μm; the porosity of the porous copper is above 30%, preferably 30-70%, more preferably 40%, 50% or 60%. The present invention adopts porous copper with the above porosity to improve the oil content of the impregnated porous copper self-lubricating bearing cage material.
[0025] In the present invention, the preparation method of the porous copper preferably includes the following steps: mixing copper powder and iron powder and then sintering to obtain a copper-iron precursor; soaking the copper-iron precursor in an acid solution to obtain the porous copper. In the present invention, based on the total molar amount of the copper powder and the iron powder as 100%, the molar fraction of the iron powder is preferably 30-70%, and more preferably 40-60%; the present invention has no special requirements for the particle size of the copper powder and the iron powder, and the particle size familiar to those skilled in the art can be adopted. In a specific embodiment of the present invention, the particle size of the copper powder is 0.5μm, and the particle size of the iron powder is 5μm; the mixing is preferably ball milling mixing, and the ball milling mixing time is preferably 18-24h; the ball milling mixing is preferably carried out in a light ball mill; the sintering is preferably plasma activated sintering, and the sintering temperature is preferably 700-8 00℃, the pressure is preferably 50-60MPa, the time is preferably 5-8min, and the heating rate to the sintering temperature is preferably 40-50℃ / min; in a specific embodiment of the present invention, the copper-iron mixed powder obtained by mixing is preferably loaded into a graphite mold for sintering; before the soaking, the copper-iron precursor is preferably cut and polished; the acid solution is preferably a sulfuric acid solution, and the mass fraction of the sulfuric acid solution is preferably 5-10%; the soaking temperature is preferably 80-90℃, and the soaking is performed until no bubbles are generated; after the soaking is completed, the obtained porous copper is preferably soaked alternately with deionized water and ethanol.
[0026] The impregnated porous copper self-lubricating bearing cage material provided by the present invention includes a supramolecular gel lubricant immersed in the pores of the porous copper. In the present invention, the supramolecular gel lubricant includes a base oil and a gel factor; the gel factor includes one or two of N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide and bis(stearate) lipoic acid aluminum; the structural formula of the N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide is shown in Formula I; the structural formula of the bis(stearate) lipoic acid aluminum is shown in Formula II;
[0027]
[0028] In the present invention, the base oil preferably includes one or more of PAO4, PAO10, 150SN and 500SN; the mass percentage of the gel factor in the supramolecular gel lubricant is preferably 1-10%; when the gel factor is N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide, the mass percentage of the gel factor in the supramolecular gel lubricant is preferably 2-3%; when the gel factor is aluminum bis(stearate) lipoate, the mass percentage of the gel factor in the supramolecular gel lubricant is preferably 5-6%. The gel factor used in the present invention can form a three-dimensional network structure through non-covalent action, realize efficient capture of the base oil, and effectively avoid the loss of lubricant inside the porous copper, improve the oil retention rate of the impregnated porous copper self-lubricating bearing cage material, especially when aluminum bis(stearate) lipoate is used, the oil retention rate at high speed can reach about 90%.
[0029] The gel-impregnated porous copper self-lubricating bearing cage material provided by the present invention has a high oil retention rate, still contains a large amount of gel lubricant after high-speed operation, has less oil loss, and has better lubrication performance; and, compared with oil-impregnated bearings with the same oil content, the gel-impregnated porous copper self-lubricating bearing cage material provided by the present invention has better tribological performance, mainly because the gel factor greatly improves the tribological performance of the base oil, and when the gel factor is aluminum distearate, it can also avoid oxidation of porous copper wear debris, thereby greatly improving the tribological performance of the material.
[0030] The present invention also provides a method for preparing the impregnated porous copper self-lubricating bearing cage material described in the above scheme, comprising the following steps:
[0031] heating and mixing the gel factor and the base oil to obtain a gel factor oil solution;
[0032] The porous copper is immersed in the gel factor oil solution and then cooled to obtain the gel-impregnated porous copper self-lubricating bearing cage material.
[0033] The present invention heats and mixes the gel factor and the base oil to obtain a gel factor oil solution. In the present invention, the temperature of the heating and mixing is preferably 170 to 190° C., specifically 170° C., 180° C. or 190° C., and the time of the heating and mixing is preferably 15 to 30 minutes.
[0034] After obtaining the gel factor oil solution, the present invention soaks the porous copper in the gel factor oil solution and then cools it to obtain the impregnated gel porous copper self-lubricating bearing retainer material. In the present invention, the immersion temperature is preferably above 160°C, more preferably 170-190°C, specifically 170°C, 180°C or 190°C; the immersion vacuum is preferably below -0.8 Bar, and the immersion time is preferably 4-10h, more preferably 5-6h. The present invention soaks under the above conditions, so that the gel factor oil solution can fully enter the tiny pores of the porous copper. After the immersion is completed, the present invention preferably cools the gel factor oil solution soaked with the porous copper to room temperature, then takes out the porous copper and wipes off the attached supramolecular gel lubricant to obtain the impregnated gel porous copper self-lubricating bearing retainer material.
[0035] The present invention also provides the use of the impregnated porous copper self-lubricating bearing cage material described in the above scheme or the impregnated porous copper self-lubricating bearing cage material prepared by the preparation method described in the above scheme in the lubrication of mechanical parts. The present invention has no special requirements for the specific method of the application, and a method familiar to those skilled in the art can be used.
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] In the following examples, N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide was prepared by the following method:
[0038] 3,4-dichlorobenzaldehyde (0.05 mol) was dissolved in 40 mL of methanol at room temperature to obtain a 3,4-dichlorobenzaldehyde solution, and then 215.8 g (0.055 mol) of a 50 wt% aqueous solution of D-gluconic acid was added to the 3,4-dichlorobenzaldehyde solution, and then concentrated hydrochloric acid (20 mL) was added under vigorous stirring. The reaction mixture was stirred for 36 h, and the white solid was collected by filtration. The filter cake was washed with water until neutral, and then washed twice with hot dichloromethane to obtain 2,4-(3,4-dichlorobenzyl)-D-gluconic acid methyl ester. Dissolve 2,4-(3,4-dichlorobenzyl)-D-gluconic acid methyl ester (0.01 mol) in 50 mL of methanol, add n-dodecylamine (0.03 mol) and DMAP (0.005 mmol), stir for 12 h, add 20 mL of water, collect the white solid by filtration, wash the filter cake twice with hot dichloromethane, and recrystallize in methanol to obtain N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide.
[0039] In the following examples, aluminum bis(stearate) lipoic acid was prepared by the following method:
[0040] Dissolve lipoic acid (0.01 mol) and stearic acid (0.02 mol) in chloroform (50 mL), add a solution of aluminum isopropoxide (0.01 mol) in chloroform (50 mL) to the solution, heat to 55° C. under stirring, and react for 6 hours. After the reaction is completed, remove the solvent in vacuo to obtain aluminum bis(stearate) lipoate.
[0041] Example 1
[0042] 32g of Cu powder (particle size 0.5μm) and 28g of Fe powder (particle size 5μm) were mixed in a light ball mill for 24h, and then the mixed powder was put into a graphite mold and sintered at 800℃, 50MPa for 5min by plasma activated sintering method, with a heating rate of 50℃ / min to obtain a Cu50Fe50 alloy precursor. After cutting and polishing, the Cu50Fe50 alloy precursor was placed in a prepared 10wt.% H2SO4 solution and heated at 90℃. When no more bubbles were generated in the solution, the porous copper sample was taken out and then alternately soaked in deionized water and ethanol, respectively, for 3 times each, and each soaking for 15min, to obtain a porous copper block M50. After testing, the average pore size of M50 was 1.9 microns and the porosity was 47%.
[0043] 0.4 g of N-dodecyl-2,4-(3,4-dichlorobenzylidene)-D-glucamide was added to 20 g of PAO10 lubricating oil, and the mixture was stirred at 180° C. for 20 min to obtain an oil solution A.
[0044] The porous copper M50 was immersed in the hot oil solution A, placed in a vacuum oven, and immersed for 5 hours at -0.8 bar vacuum and 180°C. The oil solution immersed in the porous copper was then taken out of the vacuum oven and dropped to room temperature under atmospheric pressure. The porous copper block was then taken out of the oil solution, and the excess gel on the surface of the porous copper was wiped clean with a dust-free cloth to obtain a gel-impregnated porous copper self-lubricating bearing cage material.
[0045] Example 2
[0046] 25g of Cu powder (particle size 0.5μm) and 33g of Fe powder (particle size 5μm) were mixed in a light ball mill for 24h, and then the mixed powder was put into a graphite mold and sintered for 5min at 800℃ and -50MPa by plasma activated sintering method, with a heating rate of 50℃ / min, to obtain a Cu40Fe60 alloy precursor. After cutting and polishing, the Cu40Fe60 alloy precursor was placed in a prepared 10wt.% H2SO4 solution and heated at 90℃. When no more bubbles were generated in the solution, the porous copper sample was taken out and then alternately soaked in deionized water and ethanol, respectively, for 3 times each, and each soaking for 15min, to obtain a porous copper block M60. After testing, the average pore size of M60 was 1.6 microns and the porosity was 56%.
[0047] The preparation method of oil solution A is the same as that of Example 1.
[0048] The porous copper M60 was immersed in the hot oil solution A, placed in a vacuum oven, and immersed for 5 hours at -0.8 bar vacuum and 180°C. The oil solution immersed in the porous copper was then taken out of the vacuum oven and dropped to room temperature under atmospheric pressure. The porous copper block was then taken out of the gel, and the excess gel on the surface of the porous copper was wiped clean with a dust-free cloth to obtain a gel-impregnated porous copper self-lubricating bearing cage material.
[0049] Example 3
[0050] The preparation method of the porous copper block M50 is the same as that in Example 1.
[0051] 1 g of aluminum bis(stearate) lipoate was added to 20 g of PAO10 lubricating oil, and the mixture was stirred at 170° C. for 20 min to obtain an oil solution B.
[0052] The porous copper M50 was immersed in the hot oil solution B, placed in a vacuum oven, and immersed for 5 hours at -0.8 bar vacuum and 180°C. The oil solution immersed in the porous copper was then taken out of the vacuum oven and dropped to room temperature under atmospheric pressure. The porous copper block was then taken out of the gel, and the excess gel on the surface of the porous copper was wiped clean with a dust-free cloth to obtain a gel-impregnated porous copper self-lubricating bearing cage material.
[0053] Example 4
[0054] The preparation method of the porous copper block M60 is the same as that of Example 2; the preparation method of the oil solution B is the same as that of Example 3.
[0055] The porous copper M60 was immersed in the hot oil solution B, placed in a vacuum oven, and immersed for 5 hours at -0.8 bar vacuum and 180°C. The oil solution immersed in the porous copper was then taken out of the vacuum oven and cooled to room temperature under atmospheric pressure. The porous copper block was then taken out of the gel, and the excess gel on the surface of the porous copper was wiped clean with a dust-free cloth to obtain a gel-impregnated porous copper self-lubricating bearing cage material.
[0056] Comparative Example 1
[0057] The preparation method of the porous copper block M50 is the same as that in Example 1.
[0058] The porous copper M50 was immersed in PAO10 at 180°C, placed in a vacuum oven, and immersed for 5 hours at -0.8 bar vacuum and 180°C. The PAO10 immersed in porous copper was then taken out of the vacuum oven and cooled to room temperature under atmospheric pressure. The porous copper block was then taken out of the PAO10, and the excess PAO10 on the porous copper surface was wiped clean with a dust-free cloth to obtain an oil-impregnated porous copper self-lubricating bearing cage material.
[0059] Comparative Example 2
[0060] The preparation method of the porous copper block M60 is the same as that in Example 2.
[0061] The porous copper M60 was immersed in PAO10 at 180°C, placed in a vacuum oven, and immersed at -0.8 bar vacuum and 180°C for 5 hours. The PAO10 immersed in porous copper was then taken out of the vacuum oven and cooled to room temperature under atmospheric pressure. The porous copper block was then taken out of the PAO10, and the excess PAO10 on the porous copper surface was wiped clean with a dust-free cloth to obtain an oil-impregnated porous copper self-lubricating bearing cage material.
[0062] Test Example 1
[0063] The properties of the self-lubricating bearing retainer materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested, and the specific testing method is as follows:
[0064] Using TRB produced by Anton Paar in Germany 3The tribological properties of the materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were evaluated using a ball-on-disc friction and wear tester, with the upper friction pair being a CGr15 steel ball and the lower friction pair being the self-lubricating bearing retainer material prepared in Examples 1 to 4 or Comparative Examples 1 to 2. The test conditions were: temperature 25°C, frequency 1Hz, amplitude 5mm, load 5N, and test time 30min.
[0065] The trend of the friction coefficient of the self-lubricating bearing cage material prepared in Example 1, Example 3 and Comparative Example 1 over time is shown in the figure Figure 1 As shown, the friction coefficient of the self-lubricating bearing retainer material prepared in Example 2, Example 4 and Comparative Example 2 varies with time. Figure 2 The average friction coefficient of the lubricating materials obtained in each embodiment is shown in Table 1.
[0066] Table 1 Average friction coefficient of lubricating materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2
[0067] Sample No. Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Average friction coefficient 0.17408 0.2453 0.12003 0.12047 0.32167 0.34323
[0068] According to Table 1, Figure 1 and Figure 2 It can be seen from the data in that the gel-impregnated porous copper self-lubricating bearing cage material prepared by the present invention has a significantly lower average friction coefficient and improved lubrication stability compared with the oil-impregnated porous copper self-lubricating bearing cage material in the comparative example.
[0069] Test Example 2
[0070] The oil retention rate of the self-lubricating bearing cage materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested, and the specific testing method is as follows:
[0071] The initial lubricant (gel or oil) mass m of the materials of Examples 1 to 4 and Comparative Examples 1 to 2 was recorded. The materials of Examples 1 to 4 and Comparative Examples 1 to 2 were placed in centrifuge tubes, centrifuged at 1000 rpm for 10 min, and the mass m1 of the lubricant (gel or oil) was recorded; then the centrifuge was continued at a higher speed (the speed was increased by 1000 rpm each time until 8000 rpm) for 10 min, and the mass m2 to m8 of the lubricant (gel or oil) was recorded respectively; according to the formula (oil retention rate = m i / m, i=1~8) to calculate the oil retention rate.
[0072] The oil retention test results of the self-lubricating bearing cage materials prepared in Example 1, Example 3 and Comparative Example 1 at different speeds are as follows: Figure 3 The oil retention test results of the self-lubricating bearing cage materials prepared in Example 2, Example 4 and Comparative Example 2 at different speeds are shown in Figure 4 shown.
[0073] according to Figure 3 , Figure 4 It can be seen from the data in that the oil retention rate of the porous copper self-lubricating bearing cage material impregnated with gel provided by the present invention is significantly improved compared with the porous copper self-lubricating bearing cage material impregnated with oil. In particular, when aluminum bis(stearate) lipoate is used as the gel factor (Example 3 and Example 4), the obtained cage material can still maintain a high oil content of about 90% at high speed.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A porous copper self-lubricating bearing cage material impregnated with gel, characterized in that: The invention comprises porous copper and a supramolecular gel lubricant immersed in the pores of the porous copper; the supramolecular gel lubricant comprises a base oil and a gel factor; the gel factor comprises one or two of N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide and bis(stearate) lipoic acid aluminum; and the porosity of the porous copper is above 30%.
2. The impregnated porous copper self-lubricating bearing cage material according to claim 1, characterized in that: The pore size of the porous copper is in the micron level; the porosity of the porous copper is 30-70%.
3. The impregnated porous copper self-lubricating bearing cage material according to claim 1, characterized in that: The method for preparing the porous copper preferably comprises the following steps: mixing copper powder and iron powder and sintering them to obtain a copper-iron precursor; and soaking the copper-iron precursor in an acid solution to obtain the porous copper.
4. The impregnated porous copper self-lubricating bearing cage material according to claim 1, characterized in that: The base oil includes one or more of PAO4, PAO10, 150SN and 500SN.
5. The impregnated porous copper self-lubricating bearing cage material according to claim 1, characterized in that: The mass percentage of the gel factor in the supramolecular gel lubricant is 1-10%.
6. The impregnated porous copper self-lubricating bearing cage material according to claim 1 or 5, characterized in that: When the gel factor is N-dodecyl-2,4-(3,4-dichlorobenzyl)-D-glucamide, the mass percentage of the gel factor in the supramolecular gel lubricant is 2-3%; when the gel factor is aluminum bis(stearate) lipoate, the mass percentage of the gel factor in the supramolecular gel lubricant is 5-6%.
7. The method for preparing the impregnated porous copper self-lubricating bearing cage material according to any one of claims 1 to 6, characterized in that: The following steps are involved: heating and mixing the gel factor and the base oil to obtain a gel factor oil solution; The porous copper is immersed in the gel factor oil solution and then cooled to obtain the gel-impregnated porous copper self-lubricating bearing cage material.
8. The preparation method according to claim 7, characterized in that: The temperature of the heating and mixing is 170-190° C., and the time is 15-30 minutes.
9. The preparation method according to claim 7, characterized in that: The immersion temperature is above 160° C., the vacuum degree is below -0.8 bar, and the immersion time is 4 to 10 hours.
10. Use of the impregnated porous copper self-lubricating bearing cage material according to any one of claims 1 to 6 or the impregnated porous copper self-lubricating bearing cage material prepared by the preparation method according to any one of claims 7 to 9 in lubrication of mechanical parts.
Citation Information
Patent Citations
Self-restraint lubricating composition composite material and preparation method thereof
CN105505543A
Self-lubrication oil-containing bearing containing immersion gel lubricant and preparation method of self-lubrication oil-containing bearing
CN109667835A
Nano-particle composite supermolecular gel lubricant and preparation method thereof
CN111635800A
Highly oleophylic copper nanoparticles as well as preparation method and application thereof
CN116329565A
MOFs nanoparticle composite gel lubricant and preparation method thereof
CN118085943A